Correlation Between the Presence of Psychopathological Symptoms and Internet Addiction ?mong College Students in Cyprus. - Prodromou, Maria; Iordanou, Despo; Michael, Xenia; Mamais, Ioannis (Nosileftiki)
Aim: The study is aimed to investigate psychopathological symptoms caused by Internet addiction among Cyprus College Female students in the field of aesthetics at Cyprus College of Cyprus. Material and Method: The study was conducted among 125 female undergraduate students of the Aesthetics department at Cyprus College during October 2019. Participants completed a sociodemographic questionnaire, Internet Addiction Test and Symptom Checklist-90-Revision (SCL-90-R). The questionnaires were given in a close envelope and returned in a sealed box, maintaining the principles of confidentiality and the preservation and safeguarding of the personal data of the participants in the research. Research Data were analyzed using the statistical package of Social Sciences (SPSS) version 25.0 Descriptive statistics were used for computer use characteristics. ANOVA test was used to determine the correlations between internet addiction and psychiatric symptoms. Results: The results showed that 125 female students participated in the study. The average age of graduate students was 19.24 ± 1.08. The level of Internet addiction is divided into 4 categories, which are: No, Minimal, Moderate and Excessive levels. The frequency of Internet addiction (excessive) was 5.6% (IAT score: 60--100). The frequency of moderate risk of Internet addiction was 19.4% (IAT score: 40--59). The frequency of minimal risk of Internet addiction was 43.5% (IAT score: 20--39). The frequency of no risk of internet addition was 31.5% (IAT score: 0--19) Moreover, at the same time the percentage of the sample which scored with minimal, moderate and high level of internet addiction were 68.5%. The 68.5% showed coexistence of psychopathological symptoms such as (somatization, obsessive compulsive, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation, psychoticism) and Internet addiction. Conclusions: There is a consistent and positive correlation between Internet Addiction and psychopathological symptoms such as somatization, obsessive-compulsive symptoms, interpersonal sensitivity, depression, anxiety, hostility/aggression, phobic anxiety, paranoid ideation, psychoticism. Internet enter in the middle of their relations, of their family, of their life, of their activities causes' mental distress and psychopathological symptoms that worsen the situation of miscommunication with the outside environment. The society should therefore increase the education and the social rules about the use of Internet by putting limitations in the internet use.